A systematic management algorithm for perioperative complications after robotic-assisted partial nephrectomy - Ryan, James; MacCraith, Eoin; Davis, Niall F.; McLornan, Liza (Canadian Urological Association Journal, 2019)
Nephron-sparing surgery (NSS) is the treatment of choice for T1 renal cell carcinoma (RCC). Since the first robotic-assisted partial nephrectomy (RAPN) was performed in 2004, NSS is being implemented with increasing frequency. RAPN will likely become the gold standard procedure for T1 RCC due to improved dexterity, enhanced visualization, shorter learning curve, quicker recovery time, and shortened warm ischemic time. Although RAPN appears to be the preferred treatment for select renal tumors, there are notable complications in up to 35% of cases. While complications associated with RAPN are well-described, there is a lack of literature describing appropriate management strategies. Herein, we review complications associated with RAPN and design an appropriate systematic management algorithm.